Efisiensi Pemilihan Pelat Baja pada Rehabilitasi Gedung Bertingkat terhadap Biaya dan Waktu (Studi Kasus Gedung Operasi RSUD Kota Langsa) - Arisna Fauzia; Firdasari Firdasari (Fakultas Teknik, 2022)
Increasing the use of space in the multi-storey buildings is self-requirement for the owner in making the most of function of the building. The Langsa City Hospital Operating Building with structural height of +10 meters and has two floors, with the existing part of the 2nd floor not fully designed a closed room. Currently, according to the owner's request, the function of this building is being utilized to be used as a first-floor room as an operating room, while the second floor is intended as a storage room and hall. Based on that, it is necessary to estimate against the appropriate and efficient method of slab work so that to be sure the project objectives are achieved. This paper aims to analyze the comparison between the use of steel deck and conventional deck to the study sites based on cost and time. The research method used begins with collecting field data, calculating the budget plan referring to the Work Unit Price Analysis (AHSP) contained in the contract document, then estimating the implementation time using the labor coefficient according to the 2016 AHSP. The results showed that there was a difference in the budget for the two deck slabs of Rp. 28,616,000. In addition, in terms of the duration of the completion of the work, the difference between the calculation of the estimated implementation of the conventional deck work and the realization of the implementation of the steel deck is 39 working days. Based on the results obtained, the use of steel deck is cheaper and more time efficient than the use of conventional deck. So that the selection of the use of steel deck at the study site is appropriate because it can save costs and time.